Using fuzzy logic in assessing of automated testing system - Zybin, Vladyslav Ivanovich; Liutenko, Iryna Victorivna (Одеська національна академія харчових технологій, 2020)
This document describes the use of fuzzy logic in evaluating an automated testing system. Testing is a key factor in improving software reliability. Popular automated testing systems and a brief description are introduced. Fuzzy logic and selection of quality criteria is described. A system selection formula is proposed.
Keywords: fuzzy logic; automated testing system; software; test automation frameworks; web applications; web programs